Periodic behaviour of coronal mass ejections, eruptive events, and solar activity proxies during solar cycles 23 and 24. (October 2018) - Barlyaeva, Tatiana; Wojak, Julien; Lamy, Philippe; Boclet, Brice; Toth, Imre
Abstract: We report on the parallel analysis of the periodic behaviour of coronal mass ejections (CMEs) based on 21 years [1996–2016] of observations with the SOHO/LASCO–C2 coronagraph, solar flares, prominences, and several proxies of solar activity. We consider values of the rates globally and whenever possible, distinguish solar hemispheres and solar cycles 23 and 24. Periodicities are investigated using both frequency (periodogram) and time-frequency (wavelet) analysis. We find that these different processes, in addition to following the ≈ 11-year Solar Cycle, exhibit diverse statistically significant oscillations with properties common to all solar, coronal, and heliospheric processes: variable periodicity, intermittence, asymmetric development in the northern and southern solar hemispheres, and largest amplitudes during the maximum phase of solar cycles, being more pronounced during solar cycle 23 than the weaker cycle 24. However, our analysis reveals an extremely complex and diverse situation. For instance, there exists very limited commonality for periods of less than one year. The few exceptions are the periods of 3.1–3.2 months found in the global occurrence rates of CMEs and in the sunspot area (SSA) and those of 5.9–6.1 months found in the northern hemisphere. Mid-range periods of ≈ 1 and ≈ 2 years are more wide spread among the studied processes, but exhibit a very distinct behaviour with the first one being present only in the northern hemisphere and the second one only in the southern hemisphere. These periodic behaviours likely results from the complexity of the underlying physical processes, prominently the emergence of magnetic flux. Highlights: Periodicities in CMEs, flares, prominences, and solar proxies studied for SC 23 & 24. Processes considered globally, in N/S hemispheres, and separately for SC 23 & 24. Both frequency (periodogram) and time-frequency (wavelet) analysis are applied. Limited commonality found in periods <1yr, except periods of 3.1–3.2 months. Periods of ≈1yr found exclusively in the north and of ≈2yr in the south hemispheres.